Pemberdayaan Pelaku Usaha Perikanan melalui Penyuluhan Usaha Ekonomi yang Berkelanjutan di Desa Bulo - Wijaya, Novie; Ohorella, Rafi; Triyastuti, Meilya Suzan (Indonesian Journal for Social Responsibility, 2025)
Most of the people in Bulo Village work as fishermen. Fish catches in Bulo village include tuna using kite fishing gear. Marketing of local catches, decreasing productivity of capture fisheries, and sustainability of fish resources are problems faced by fisheries business actors. The purpose of this service activity is for partners to understand and be able to increase knowledge of sustainable economic businesses for fisheries business actors in Bulo village. The methods used in this service are conducting field surveys and interviews directly with partners, counseling on sustainable economic businesses, and evaluating community service activities. The topics discussed in the community service program included the potential of fishery businesses, steps to start a small-scale fishery business and its management, diversification of processed fishery products and product licensing legality, digital marketing and product branding, microfinance, and access to capital. The results of the evaluation of this community service activity are increasing the knowledge of partners in sustainable economic business.